Experimental investigation on thermal runaway propagation of 18, 650 lithium-ion battery modules with two cathode materials at low pressure. (15th July 2022) - Jia, Zhuangzhuang; Huang, Zonghou; Zhai, Hongju; Qin, Pen; Zhang, Yue; Li, Yawen; Wang, Qingsong
Abstract: As lithium-ion batteries (LIBs) are becoming more widely applied in aviation, growing attention has been paid to thermal runaway (TR) propagation due to its high complexity in unique low-pressure environments. This paper investigates the characteristics of TR propagation for the LiFePO 4 and LiNi 0.5 Co 0.2 Mn 0.3 O 2 modules at 95, 70, and 35 kPa. Some critical parameters in LIB modules, such as TR behavior, temperature, and propagation speed are analyzed. The results indicate that TR behaviors become weaker and the average maximum temperature of modules decreases 20–50 °C as the pressure decreases. The TR time of the LiFePO 4 module decreases from 1218 to 603 s, when the pressure decreases from 95 to 35 kPa, but the LiNi 0.5 Co 0.2 Mn 0.3 O 2 module increases from 33 to 151 s, indicating a reduction in the TR propagation time of 50.1% for the LiFePO 4 module but an increase of 357.6% for the LiNi 0.5 Co 0.2 Mn 0.3 O 2 module. As the pressure decreases, the mass losses of modules decrease, but the impact force of the LiNi 0.5 Co 0.2 Mn 0.3 O 2 battery safety venting increases. Finally, a heat transfer model is established to explain the trend in TR influence at low pressure. This work clarifies the TR propagation characteristics of LIBs with two cathodes, which can help improve the safe use of LIB modules at low pressure. Highlights: Pioneering study on thermal runaway propagation at low pressure. The safety venting of LFP and NCM batteries is further studied at low pressure. Thermal runaway propagation features at low pressures are verified by theory.